Long-Term Treatment Outcomes for Parent-Assisted Social Skills Training for Adolescents With Autism Spectrum Disorders: The UCLA PEERS Program - Mandelberg, Josh; Laugeson, Elizabeth Ann; Cunningham, Tina D.; Ellingsen, Ruth; Bates, Shannon; Frankel, Fred (Journal of mental health research in intellectual disabilities, 2014)
Social deficits are a hallmark characteristic among adolescents with autism spectrum disorders (ASD), yet few evidence-based interventions exist aimed at improving social skills for this population, and none have examined the maintenance of treatment gains years after the intervention has ended. This study examines the durability of the Program for the Education and Enrichment of Relational Skills (PEERS), a manualized, parent-assisted social skills intervention for high-functioning adolescents with ASD. Targeted skills related to the development and maintenance of friendships were assessed 1-5 years following treatment for 53 adolescent participants and their parents. Results indicate that adolescents receiving PEERS maintained treatment gains at long-term follow-up on standardized measures of social functioning including the Social Skills Rating System and the Social Responsiveness Scale as well as in frequency of peer interactions and social skills knowledge. Perhaps due to parent involvement in treatment, results reveal additional improvements in social functioning at follow-up assessment.